EVALUASI PENERAPAN AKUNTANSI SEKTOR PUBLIK UNTUK MENCEGAH FRAUD PADA SEKTOR PUBLIK DI KANTOR SEKRETARIAT DAERAH KABUPATEN KOLAKA - Rosdiana, Rosdiana; Triani, Neks; Syahrir, Sasmita Nabila (Komunitas Manajemen Kompetitif, 2025)
This study aims to evaluate the implementation of public sector accounting in preventing fraud practices at the Regional Secretariat Office of Kolaka Regency. The method used is qualitative descriptive research with data collection techniques through interviews, observations, and documentation. Data analysis techniques follow an interactive model that includes data reduction, data presentation, and drawing conclusions. The results of the study indicate that the implementation of an effective public sector accounting model, including transparency, accountability, and compliance with regulations, contributes significantly to preventing fraud practices. The internal control system implemented also strengthens these prevention efforts. Keywords: fraud prevention, publik sector accounting, transparency